Memahami Variasi Lingkungan Lokal melalui Interaksi Tanah-Air-Vegetasi di Lanskap Perkebunan Moat - Nur Meyla Ulfiana Botutihe; Wa Nini (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
This study aimed to analyze soil–water–vegetation interactions at multiple observation points within the plantation landscape surrounding Lake Moat, Indonesia. Six soil sampling points and two surface water points were selected to represent differences in micro-landscape conditions. Soil parameters, including pH, electrical conductivity (EC), total dissolved solids (TDS), temperature, and salinity, were measured in situ, while dominant vegetation species were identified as ecological indicators. The results showed consistently acidic soil conditions (pH 4.0–5.5) with clear variation in EC and TDS, separating the sampling points into two main groups (T1–T3 and T4–T6). Points with lower pH generally exhibited higher EC and TDS values, indicating differences in ion accumulation among observation points. In contrast, surface water parameters showed relatively stable conditions with near-neutral pH and narrower variation. Differences in dominant vegetation, from grasses at low-EC points to shrubs at high-EC points, further reflected ecological responses to soil chemical conditions. These findings confirm that local environmental heterogeneity is an inherent characteristic of the Moat plantation landscape and provide a basis for adaptive land management in tropical highland ecosystems.